2010
DOI: 10.1002/cjoc.201190029
|View full text |Cite
|
Sign up to set email alerts
|

CuO Crystalline Modified Glassy Carbon Electrodes for Anodic Amperometric Determination of Hydrogen Peroxide

Abstract: As an alternative selection of electrocatalytic surface modifier, the electrochemically generated copper oxides is reinvestigated by using cyclic voltammetry (CV), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). Interesting phenomena have been found, which indicate that the electrodeposition from the Cu 2+ solution under cyclic voltammetric conditions can generate a transparent Cu(OH) 2 crystalline on the surface of glassy carbon electrodes, and this crystalline can be further tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Upon the addition of H 2 O 2 to a 0.10 M NaOH solution, an obvious increase of oxidation current could be seen and it constantly increased with increasing H 2 O 2 concentration (Figure A), implying that the ZIF-8 shell did not affect the diffusion of H 2 O 2 . According to previous literatures, the reaction mechanism could be thought as follows: first, Cu + (i.e., Cu 2 O) was converted to Cu 2+ (i.e., Cu­(OH) 2 , CuO), and then to Cu 3+ (i.e., CuOOH) by electrochemical oxidation in alkaline media. Subsequently, H 2 O 2 was oxidized by Cu 3+ (i.e., CuOOH), and Cu 2+ was regenerated.…”
Section: Resultsmentioning
confidence: 99%
“…Upon the addition of H 2 O 2 to a 0.10 M NaOH solution, an obvious increase of oxidation current could be seen and it constantly increased with increasing H 2 O 2 concentration (Figure A), implying that the ZIF-8 shell did not affect the diffusion of H 2 O 2 . According to previous literatures, the reaction mechanism could be thought as follows: first, Cu + (i.e., Cu 2 O) was converted to Cu 2+ (i.e., Cu­(OH) 2 , CuO), and then to Cu 3+ (i.e., CuOOH) by electrochemical oxidation in alkaline media. Subsequently, H 2 O 2 was oxidized by Cu 3+ (i.e., CuOOH), and Cu 2+ was regenerated.…”
Section: Resultsmentioning
confidence: 99%
“…In several instances lower detection limits have been reported than those found at enzymatic sensors. 46,128,[137][138][139] Several successful examples of these non-enzymatic peroxide sensors have been demonstrated by Bolshakov et al 46 and Lupu et al, 128 who both reported a LOD of 1 nM for their PB films. The former utilised electrodeposited PB on Au microelectrodes, whilst the latter used a polystyrene-based physical templating method to co-deposit polypyrrole and PB.…”
Section: Analytical Areas Of Interest Environmental Sensingmentioning
confidence: 99%
“…Copper and copper oxides have also been studied for their ability to sense peroxide. Lin et al 139 electrodeposited Cu on a glassy carbon electrode, followed by an electrochemical oxidation procedure in 10 mM NaOH. This produced a CuO film which was found to possess a LOD towards peroxide of 25 nM.…”
Section: Analytical Areas Of Interest Environmental Sensingmentioning
confidence: 99%
“…There have been several efforts to detect carbohydrates using nanostructured CuO. In addition, other researchers have fabricated nanosensors containing CNTs and metals/metal oxides using various techniques [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%